2020
DOI: 10.31234/osf.io/yse56
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Psychopathology and positive emotions in daily life

Abstract: In this short review, we describe recent trends from research investigating positive affect (PA) in daily life in relation to mood disorders. Aside from notable exceptions (e.g., mania), most mood disorders involve relatively lower levels of PA in daily life, often combined with a larger level of variability in PA. In reaction to positive events, studies show a puzzling “mood brightening” effect in individuals with mood disorder symptoms that suggests hyper responsiveness to real-life rewards. Studies into anh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 54 publications
0
2
0
Order By: Relevance
“…Likewise, Kiken et al (2017) , in their nine-week field study, demonstrated that positive emotions predicted psychological health, in particular for those who were more mindful and for those who tended to savor the moment. Heininga and Kuppens (2021) , in their review of ecological momentary assessment studies on positive emotions, highlighted that positive emotions were negatively related to mood disorders. Kwok and Fang (2021) , in a longitudinal study with students, showed that positive emotions positively predict positive meaning, strengths use, and academic engagement.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Likewise, Kiken et al (2017) , in their nine-week field study, demonstrated that positive emotions predicted psychological health, in particular for those who were more mindful and for those who tended to savor the moment. Heininga and Kuppens (2021) , in their review of ecological momentary assessment studies on positive emotions, highlighted that positive emotions were negatively related to mood disorders. Kwok and Fang (2021) , in a longitudinal study with students, showed that positive emotions positively predict positive meaning, strengths use, and academic engagement.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Villanueva, Silton, Heller, Barch, and Gruber [30] reflect on the current state of this field and outline seven challenges, with a focus on substance use. Heininga and Kuppens [31] focus on recent findings from ecological momentary assessment research investigating positive affect in relation to mood disorders. Using this method, fluctuations in positive affect can be recorded, modelled, and related to specific daily-life events.…”
Section: Psychopathologymentioning
confidence: 99%